2013
DOI: 10.1093/ckj/sft142
|View full text |Cite
|
Sign up to set email alerts
|

Overlap between dermatomyositis and ANCA vasculitides

Abstract: We present the second report of the association between antineutrophil cytoplasm antibodies (ANCA)-associated vasculitis with dermatomyositis (DM). A 47-year-old woman suddenly developed rapidly progressive renal failure in the context of (DM). The kidney biopsy showed focal and segmental necrotizing glomerulonephritis with crescent formation. Cyclophosphamide treatment was commenced resulting in a significant recovery of kidney function and maintenance of recovery at 6 months. Although the pathophysiology is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The mechanism of peripheral nervous system involvement in patients with DM is assumed to involve vascular endothelial injury in the peripheral nerves and overproduction of vascular endothelial growth factor . The occurrence of systemic vasculitis in other organs in patients with DM supports such a mechanism . Our literature survey of the nerve conduction and sural nerve biopsy studies in patients with DM‐related neuropathy mostly suggested axonal neuropathy, which is also consistent with a vascular mechanism .…”
Section: Discussionsupporting
confidence: 61%
“…The mechanism of peripheral nervous system involvement in patients with DM is assumed to involve vascular endothelial injury in the peripheral nerves and overproduction of vascular endothelial growth factor . The occurrence of systemic vasculitis in other organs in patients with DM supports such a mechanism . Our literature survey of the nerve conduction and sural nerve biopsy studies in patients with DM‐related neuropathy mostly suggested axonal neuropathy, which is also consistent with a vascular mechanism .…”
Section: Discussionsupporting
confidence: 61%
“…We conducted an additional literature search and retrieved case reports describing the association of PM or DM with a variety of pathological glomerular lesions, including mesangial proliferative glomerulonephritis [21][22][23][24][25], membranous nephropathy [26][27][28][29][30][31], membranoproliferative glomerulonephritis [32], IgA nephropathy [33][34][35][36][37], diffuse proliferative glomerulonephritis [38], immune complex-type glomerulonephritis [39][40][41][42], acute interstitial nephritis [43], lipoid nephrosis and focal glomerulosclerosis [44], focal segmental glomerulosclerosis with evidence of acute tubular injury [45], sclerotic GN with fibrocellular crescent [46], and crescentic glomerulonephritis associated with malignancy [47]. Cases presenting with anti-neutrophil cytoplasmic antibody-associated glomerulonephritis in the context of DM have also been reported [48][49][50]. As pointed out in previous studies [6,25], there is a tendency for mesangial proliferative glomerulonephritis to be more frequently observed in PM, while membranous nephropathy is more frequently observed in the context of DM.…”
Section: Discussionmentioning
confidence: 99%
“…Both prior patients also initially presented with dermatomyositis and minimal, if any, overt inflammatory muscle pathology. The patient described by Kawai et al (1), in 2011, had a 10-year history of dermatomyositis, while the patient described by Yuste et al (2), in 2014, developed both diseases within months of each other. As in the case presented here, both patients were p-AN-CA/MPO-positive with confirmatory renal biopsies and without documentation of pulmonary involvement.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been only two other reported cases of patients with dermatomyositis who subsequently developed an AN-CA-associated vasculitis (AAV) (1,2). Both prior patients also initially presented with dermatomyositis and minimal, if any, overt inflammatory muscle pathology.…”
Section: Discussionmentioning
confidence: 99%